Increased melanocytic nevi and lentigines in two patients with harlequin ichthyosis. Issue 1 (25th November 2019) - McKenzie, Shanice; Arzeno, Julia; Lonowski, Sarah; Cheng, Carol E.; Hogeling, Marcia
Abstract: An increased number of melanocytic nevi and lentigines have been reported in patients with two types of autosomal recessive congenital ichthyosis (ARCI): lamellar ichthyosis and nonbullous congenital ichthyosiform erythroderma. These melanocytic lesions may have clinical and dermoscopic features of atypia, necessitating close surveillance. Here, we report two interesting cases of pediatric patients with harlequin ichthyosis (HI) who developed increased melanocytic nevi and lentigines. These cases are unique in that the patients presented at a younger age and one patient had a darker skin phototype than previously described in the literature.